LITERATURE REVIEW INDIVIDUAL PERCEPTIONS AND DECISION MAKING: BIBLIOMETRIC ANALYSIS - Ismawati; Sopiah (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
One of the ups and downs of realization in the company is a belief and perception in making decisions about the individual himself. Various factors that influence decision making, namely decision making decision privacy , attitude individual , knowledge about risk and protection , trust in others trust in ability for protect information and considerations . In study this for obtain data using analysis bibliometrics . Article data study this collected through the Google Scholar software. The purpose of this study is to provide an overview of the topic "individual perception and decision making". The data obtained are 50 articles that have been analyzed in this study. In study this using the database obtained in 2017 to 2021 and taking the data using PoP software for find the data you need . The next process is the data that has been obtained then processed for analysis _ use Vosviewer for obtain co-authorship, co- occurance and citation data. Research results this show that topic about perception individual and taking decision really important in something organization and life everyday , however because limitations previous research that has not there is discuss about linkages topic this , so make study this less than optimal for look for related information _ with topic that